Computer Networks 18th Conference, CN 2011, Ustron, Poland, June 14-18, 2011. Proceedings - Kwiecien, Andrzej; Gaj, Piotr; Stera, Piotr (Communications in Computer and Information Science, 2011)
This book constitutes the refereed proceedings of the 18th Conference on Computer Networks, CN 2011, held in Ustron, Poland, in June 2011. The 50 revised full papers presented were carefully reviewed and selected for inclusion in the book. The papers can be divided into the following subject groups: molecular networks; network issues related to nano and quantum technology; new technologies related to the Computer Networks; fundamentals of computer networks architecture and programming; internet networks; data security in distributed systems; industrial computer networks; applications of computer networks.